Gut mucosal-associated microbiota better discloses inflammatory bowel disease differential patterns than faecal microbiota. Issue 5 (May 2019) - Altomare, Annamaria; Putignani, Lorenza; Del Chierico, Federica; Cocca, Silvia; Angeletti, Silvia; Ciccozzi, Massimo; Tripiciano, Costanza; Dalla Piccola, Bruno; Cicala, Michele; Guarino, Michele Pier Luca
Abstract: Background: Growing evidence supports the potential role of intestinal microbiota in the pathophysiology of inflammatory bowel diseases (IBD) even if the literature does not reveal uniform alterations. The aim of the study was to evaluate the mucosal (MM) and faecal microbiota (FM) composition in a cohort of IBD patients compared to healthy controls (CTRLs). Methods: Faecal and mucosal samples were collected from 14 IBD patients and 11 CTRLs. The V1-V3 region of 16S rRNA locus was amplified on a 454-Junior Genome Sequencer. Reads were grouped into operational taxonomic units (OTUs) at a sequence similarity level of 97% for taxonomic assignment, and aligned for OTUs matching against Greengenes database. Results: Irrespective of disease localization and activity, in the MM of IBD patients a statistically significant increase of Proteobacteria (especially Enterobacteriaceae, Acidaminococcus, Veillonella dispar ) and decrease of Firmicutes (especially Roseburia and Faecalibacterium prausnitzii ) and Actinobacteria was found compared to CTRLs. In the colon district some specific bacterial biomarkers were identified: Enterobacteriaceae for IBD stools, Bacteroides for IBD biopsies, Mogibacteriaceae, Ruminococcaceae and Prevotella for CTRL stools, Ruminococcaceae for CTRL biopsies. Conclusions: The profiles of FM were more similar to CTRLs, suggesting that microbiota adhering to the gut mucosa better discriminates patients from controls, with the identification of some interesting biomarkers.